Pengaruh Extraversion dan Neuroticism terhadap Audit Judgment - Puthri Yori Selsavinna; Nayang Helmayunita (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to determine and analyze the influence of the big five personality on audit judgment. This research is included in the type of causality associative research using a quantitative approach. Researchers collected data using questionnaires which were distributed to 100 auditor respondents who work in public accounting firms in the cities of Padang, Pekanbaru and Batam. The data used in this research is primary data. Testing the hypothesis in this study using multiple linear regression analysis with IBM SPSS. The results of this study indicate that extra-version have an influence on audit judgment. while neuroticism and have no effect on audit judgment. Future research can use new variables or expand the population in future research.